Illness Perception of Patients with Familial Hypercholesterolaemia varies with Level of Education and Presence of Cardiovascular Disease - Razali, Salmi; Ismail, Zaliha; Abdullah, Najib; Nawawi, Hapizah M (Environment-Behaviour Proceedings Journal, 2019)
Illness perception determines the healthy lifestyle of patients with Familial Hypercholesterolaemia (FH).Â Despite the availability of advanced treatment and preventive measures, there is still sparse data on illness perception of FH patients. Hence, this study aimed to describe the illness perception of FH patients and investigate its association with sociodemographic and illness-related factors. 100 FH patients were assessed using Pro forma questionnaires and revised illness perception questionnaire (IPQ-R). Illness perception of FH patients varies according to the level of education and the presence of cardiovascular disease (CVD). These findings may help clinicians to improve the interventions suitable for FH patients.Â Â Keywords: Familial hypercholesterolaemia; illness perception; sociodemography; cardiovascular disease eISSN: 2398-4287 Â© 2019. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open-access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peerâ€“review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/e-bpj.v4i10.1620